MTHFR C677T polymorphism and cerebrovascular lesions in elderly patients with CSVD: A correlation analysis - Li, Zhuoran; Wu, Xiaoyan; Huang, Haowei; Xu, Fan; Liang, Guangtie; Lin, Chuying; Qin, Qinbao; Lei, Xiuxia; Zeng, Xuwen; Jiang, Xinqing; Wei, Xinhua (Frontiers in Genetics, 2022)
The plasma homocysteine(Hcy) has been identified as a potential risk factor for cerebral small vessel disease. Cerebral small vessel disease (CSVD) can lead to cognitive impairment, depression and other symptoms, and is a common disease in middle-aged and elderly people. To investigate the relationship between 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and CSVD in elderly patients. Plasma levels of homocysteine (Hcy) and MTHFR genotyping were assessed. MRI and MRA were performed at the same time to analyze the relationship between different genotypes and cerebrovascular lesions. We show that Hcy plasma levels in the TT group were significantly higher than those of CC and CT groups. Moreover, we observed that the severity of white matter lesions was associated with women and positively correlated with age, previous coronary heart disease, luminal infarction and MTHFR polymorphism. The multivariate logistic regression analysis showed that age, TT genotype and lacunar infarction were independent risk factors for white matter hyperintensity (WMH). Importantly, we showed that there was a significant correlation between Hcy plasma levels and MTHFR gene polymorphism, with the TT genotype constituting an independent risk factor for WMH. Therefore, we recommended early detection of MTHFR gene polymorphisms with concomitant early intervention concerning risk factors to delay the occurrence of cognitive impairment in the CSVD elderly patients.